Diagnostic accuracy of high-resolution melting curve analysis for discrimination of oncology-associated mutations: a systematic review and meta-analysis - Shu Yu; Yan Cheng; Chen-Cheng Tang; Yue-Ping Liu (Journal of International Medical Research)
Objective To investigate the diagnostic value of high-resolution melting (HRM) analysis for oncology-associated epidermal growth factor receptor ( EGFR) gene mutations. Methods We systematically searched Embase, PubMed, and Web of Science for HRM and EGFR mutation detection studies published through September 2024. True and false positives and negatives were extracted to evaluate the diagnostic accuracy of HRM to detect EGFR mutations. The study was registered at INPLASY (INPLASY202490062). Results Twenty-six articles were obtained from 416 references. The overall diagnostic sensitivity and specificity were high at 0.95 [95% confidence interval (CI), 0.94–0.96] and 0.99 (95% CI, 0.99–0.99), respectively. Other indicators, including the positive likelihood ratio, negative likelihood ratio, and diagnostic odds ratio, were 144.91 (95% CI: 69.07–304.04), 0.08 (95% CI: 0.04–0.13), and 2405.21 (95% CI: 1231.87–4696.13), respectively. The Q value of the summary receiver operating characteristic curve was 0.979, and the area under the curve was 0.997. Conclusion As a pre-screening method, the high specificity, sensitivity, low cost, rapid turnaround, and simplicity of HRM make it a good alternative for clinical practice, but positive results must still be obtained for diagnostic confirmation. This study provides a transparent overview of relevant studies in design and conduct.